Hiatal ulcer hernia; Reflux esophagitis and Barret's ulcer. Thal operation - Suiffet, Walter; Estapé, Gonzalo (Cirugía del Uruguay, 1975)
A case of severe esophageal stenosis due to reflux ·csophagitis, with esophageal shortening and Barrett.'s ulcer was treated with the procedure of fundic patch described by Thal, with satisfactory long-term results. The present work discusses the different techniques proposed to solve this situation.